Genome editing, gene drives, and synthetic biology: Will they contribute to disease-resistant crops, and who will benefit? - Pixley, Kevin V.; Falck-Zepeda, José B.; Giller, Ken E.; Glenna, Leland L.; Gould, Fred; Mallory-Smith, Carol; Stelly, David M.; Stewart, C. Neal (Annual Reviews, 2019)
Genetically engineered crops have been grown for more than 20 years, resulting in widespread albeit variable benefits for farmers and consumers. We review current, likely, and potential genetic engineering (GE) applications for the development of disease-resistant crop cultivars. Gene editing, gene drives, and synthetic biology offer novel opportunities to control viral, bacterial, and fungal pathogens, parasitic weeds, and insect vectors of plant pathogens. We conclude that there will be no shortage of GE applications to tackle disease resistance and other farmer and consumer priorities for agricultural crops. Beyond reviewing scientific prospects for genetically engineered crops, we address the social institutional forces that are commonly overlooked by biological scientists. Intellectual property regimes, technology regulatory frameworks, the balance of funding between public- and private-sector research, and advocacy by concerned civil society groups interact to define who uses which GE technologies, on which crops, and for the benefit of whom. Ensuring equitable access to the benefits of genetically engineered crops requires affirmative policies, targeted investments, and excellent science.